2001
DOI: 10.2105/ajph.91.9.1424
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Behavior Among US Latino Men and Women From Different Countries of Origin

Abstract: Older, US-born, and more-educated respondents were less likely to be current smokers. Respondents of Puerto Rican and Cuban origin were more likely to smoke. Acculturation has divergent effects on smoking behavior by sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
179
5
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(201 citation statements)
references
References 23 publications
15
179
5
2
Order By: Relevance
“…Past research has found that foreign-born Latino men are more likely to smoke compared to their female compatriots and that, viewed collectively, a smaller percent of all foreign-born Latino adults smoke compared to all US-born adults and to other US-born minority groups separately (except for Asians). [24][25][26] These results should be interpreted with some caution, however, given that Latino immigrants are also more likely to underreport smoking behavior. 27 And, it is important to note when considering factors influencing Latino immigrant smoking, especially "acculturation," which has often been viewed simply as an individual-level adjustment process, that the tobacco industry has developed strategies to market directly to foreign-born Latin American populations in the USA.…”
Section: Introductionmentioning
confidence: 80%
“…Past research has found that foreign-born Latino men are more likely to smoke compared to their female compatriots and that, viewed collectively, a smaller percent of all foreign-born Latino adults smoke compared to all US-born adults and to other US-born minority groups separately (except for Asians). [24][25][26] These results should be interpreted with some caution, however, given that Latino immigrants are also more likely to underreport smoking behavior. 27 And, it is important to note when considering factors influencing Latino immigrant smoking, especially "acculturation," which has often been viewed simply as an individual-level adjustment process, that the tobacco industry has developed strategies to market directly to foreign-born Latin American populations in the USA.…”
Section: Introductionmentioning
confidence: 80%
“…32 The U.S. Census Bureau does not cross-tabulate specific Spanish-origin groups; breakdowns are presented only for Hispanics as a whole. Grouping Hispanics without consideration for social, historical, cultural, health, and socioeconomic distinctions 33,34 hampers our understanding of lifestyle differences impacting behavior. 35 It was our goal to describe physical activity among a subgroup on the rise, whose origins or ancestors derive primarily from the Caribbean/Atlantic islands.…”
Section: Distinctions Between Hispanic Subgroupsmentioning
confidence: 99%
“…All RS would be important to address with Latino smokers and Pleasure to Smoke, Addictive Smoking, and Social Smoking are especially important to address among converted nondaily Latino smokers. At a population level, Latinos tend to be low frequency smokers (Perez-Stable et al, 2001;Zhu, Pulvers, Zhuang, & BaezcondeGarbanati, 2007), therefore discovering possible targets for discussion in counseling this group is important. For the most sensitive interventions, it would be advised to assess smoking history to distinguish between native and converted nondaily smoking status.…”
Section: Discussionmentioning
confidence: 99%